PHYSICAL ACTIVITY VALUATION: A DISCUSSION ON AN IDENTIFIED IDEA NOT CONTEXTUALIZED IN THE LITERATURE - da Silva, Ana Flávia Andalécio Couto; Papini, Camila Bosquiero; Sebastião, Emerson; Brunheroti, Karina; Andaki, Alynne Christian Ribeiro; Kokubun, Eduardo [UNESP] (Universidade Federal do Rio Grande do Sul, 2023)
The valuation of physical activity has not yet been established as a concept or definition in the literature. Thus, the objective of the present study was to understand the concept and foster a preliminary discussion about the valuation of physical activity, through a systematic literature review followed by an integrative review with different search strategies. Considering the systematic review inclusion criteria, studies addressing the concept or definition of physical activity valuation were not identified. However, from the selection and reading of the articles in the integrative review, we sought to understand in which contexts the studies about physical activity valuation methods were developed. It is suggested that the valuation of physical activity is associated with the importance given by the individuals to physical activity, i.e. a broad concept related to value judgment regarding physical activity; the valuation of physical activity can be related to the hedonic pricing, the contingent valuation, and the avoided costs.
EVALUACIÓN DE LA ACTIVIDAD FÍSICA: DISCUSIÓN SOBRE UNA IDEA IDENTIFICADA PERO NO CONTEXTUALIZADA EN LA LITERATURA
VALORAÇÃO DA ATIVIDADE FÍSICA: DISCUSSÃO SOBRE UMA IDEIA IDENTIFICADA MAS NÃO CONTEXTUALIZADA NA LITERATURA
Keywords: Attitude; Concept formation; Decision making; Judgement